Clinical and Molecular Epidemiology of Community-Onset Bacteremia Caused by Extended-Spectrum β-Lactamase-Producing Escherichia coli over a 6-Year Period - Kang, Cheol-In; Cha, Min Kyeong; Kim, So Hyun; Ko, Kwan Soo; Wi, Yu Mi; Chung, Doo Ryeon; Peck, Kyong Ran; Lee, Nam Yong; Song, Jae-Hoon (Journal of Korean medical science, 2013)
Although extended-spectrum β-lactamase-producing Escherichia coli (ESBL-EC) has emerged as a significant community-acquired pathogen, there is little epidemiological information regarding community-onset bacteremia due to ESBL-EC. A retrospective observational study from 2006 through 2011 was performed to evaluate the epidemiology of community-onset bacteremia caused by ESBL-EC. In a six-year period, the proportion of ESBL-EC responsible for causing community-onset bacteremia had increased significantly, from 3.6% in 2006 to 14.3%, in 2011. Of the 97 clinically evaluable cases with ESBL-EC bacteremia, 32 (33.0%) were further classified as healthcare-associated infections. The most common site of infection was urinary tract infection (n=35, 36.1%), followed by biliary tract infections (n=29, 29.9%). Of the 103 ESBL-EC isolates, 43 (41.7%) produced CTX-M-14 and 36 (35.0%) produced CTX-M-15. In the multilocus sequence typing (MLST) analysis of 76 isolates with CTX-M-14 or -15 type ESBLs, the most prevalent sequence type (ST) was ST131 (n=15, 19.7%), followed by ST405 (n=12, 15.8%) and ST648 (n=8, 10.5%). No significant differences in clinical features were found in the ST131 group versus the other group. These findings suggest that epidemic ESBL-EC clones such as CTX-M-14 or -15 type ESBLs and ST131 have disseminated in community-onset infections, even in bloodstream infections, which are the most serious type of infection.